Two component oxide compositions based on TiO2 rutile: ultrasonic treatment, their physicochemical and photocatalytic properties - Kiziun, Olena V.; Sachuk, Olena V.; Zazhigalov, Valery O.; Zabolotnii, Yevhenii V.; Kotynska, Ludmila Y. (V.P. Kukhar Institute of Bioorganic Chemistry and Petrochemistry of the National Academy of Sciences of Ukraine, 2025)
The creation of oxide two-component systems based on TiO2 rutile was studied. Influence of ultrasound treatment (UST) of these mixtures on their properties was established. The mixtures treatment less influences on the ratio of intensity of (110)/(101) reflexes of TiO2 what testify any structural change of this oxide but in same time little increase of its particles size was observed. The little increase of the dimension particles for second oxide after UST for the studied mixtures excluding TiO2/MgO and TiO2/ZnO was observed. The partial transformation of MgO to Mg(OH)2 as result of TiO2/MgO composition treatment was shown which accompanied by decrease of MgO particles size. In the case of TiO2/ZnO composition the partial destruction of ZnO was observed. The increase of the pores radius after UST with the change of surface element ratio determined by EDX method can testify that strong interaction between oxides takes place. This fact leads to an increase the band gap for the mixture in comparison with initial TiO2 with its average value between characteristic for TiO2 and other oxide in mixture. The study of photocatalytic properties of the samples in metronidazole (MN) oxidative decomposition in water shows that for all compositions, excluding TiO2/ZnO where the activity is connected with more active ZnO in this reaction but not TiO2, a decrease of initial rate constant Kd was observed. The reduction of rate constant was connected with a decrease of TiO2 content in the mixtures and introduced value of rate constant determined to quantity of TiO2 demonstrate its increase in comparison to individual TiO2.This fact testify the strong interaction in complexes systems between two oxides. Obtained result permits to realize the MN photocatalytic degradation in water with an increase of the complexes catalyst content in reaction mixture what leads to an increase both rate constant and degree of antibiotic transformation. It was established that UST increased the stability of the samples in MN transformation and as result the conversion of MN has more value than in initial mixtures. An increase of degradation degree after UST of the samples correlates with the growth of medium pore radius in result of this treatment what can be connected with an increase of sample surface accessible to UV irradiation. It was shown that obtained composites demonstrate better properties in MN destruction in water in comparison with data known from the literature.